Absorption performance of biomass hollow pyramidal microwave absorber using multi-slot array technique - Mas Izzati Fazin; Ahmad Rashidy Razali; Mohd Nasir Taib; Norhayati Mohamad Noor; Linda Mohd Kasim; Nazirah Mohamat Kasim; Hasnain Abdullah Idris (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Electromagnetic interference (EMI) is an undesired electromagnetic (EM) wave by nearby electronic devices, process equipment, and measuring instruments. In this work, a novel multi-slot technique is applied to the hollow biomass pyramidal microwave absorber to study its absorption properties thoroughly. Two different slot arrangements in horizontal and vertical configuration are designed for the proposed microwave absorbers. Both slot design concepts have identical shape and size. This work aims to study, compare and analyze the absorption performance of the proposed designs at L, S, C and X frequency bands. The biomass material is used to form as absorbent material. The characteristics performance of the multi-slot design on biomass hollow pyramidal microwave absorbers are measured by using naval research laboratory (NRL) Arch space-free method. The frequency range set up for the measurement is in between 1 GHz to 12 GHz. The multi-vertical slots design exhibits better absorption performance at C-band and X-band which is -63.67 dB and -46.78 dB respectively while the multi-horizontal slots design provides better absorption performance at S-band which is -16.92 dB. The results shows that both design performances are frequency-dependent since horizontal slots design improve maximum absorption performance at low frequency while vertical slots design delivers better performance at high frequency.